PENGARUH MOTIVASI DAN PEMBERIAN INSENTIF TERHADAP KINERJA KARYAWAN DI DEPARTEMEN PENJUALAN PT. TIRTA SARANA SUKSES - SOFYAN LAZUARDI (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2015)
Human Resources (HR) is a very important aspect for the company which humans as plan, organize, manage, and control every activity in the company. So that HR in a company should be maximized in order to be workers who have a good quality performance to achieve the objectives of the company to the fullest. PT Tirta Sarana Sukses pointed out as one of the factors influential to motivate and drive the performance of employees. Expected to give a definite incentive for employees to cope with the risks of socio-economic and programs covering all types of basic protection needed by employees will be able to boost the spirit and morale of employees. Effect of motivation on employee performance is the result of testing the hypothesis (H1) This test is statistically proven that motivation has positive influence on employee performance. It means that there is the influence of variables Motivation on Employee Performance in PT. Tirta Sarana Sukses, (2) the effect of incentives on employee performance is a result of testing the hypothesis (H2) This test is statistically proven that incentives positive influence on employee performance. It means that there is the influence of variables Incentives for Employee Performance PT. Tirta Means Success.